Systematic review of the performance of HIV viral load technologies on plasma samples. - Kimberly A Sollis; Pieter W Smit; Susan Fiscus; Nathan Ford; Marco Vitoria; Shaffiq Essajee; David Barnett; Ben Cheng; Suzanne M Crowe; Thomas Denny; Alan Landay; Wendy Stevens; et al. (PLoS ONE)
Background Viral load (VL) monitoring is the standard of care in developing country settings for detecting HIV treatment failure. Since 2010 the World Health Organization has recommended a phase-in approach to VL monitoring in resource-limited settings. We conducted a systematic review of the accuracy and precision of HIV VL technologies for treatment monitoring. Methods and findings A search of Medline and Embase was conducted for studies evaluating the accuracy or reproducibility of commercially available HIV VL assays. 37 studies were included for review including evaluations of the Amplicor Monitor HIV-1 v1.5 (n = 25), Cobas TaqMan v2.0 (n = 11), Abbott RealTime HIV-1 (n = 23), Versant HIV-1 RNA bDNA 3.0 (n = 15), Versant HIV-1 RNA kPCR 1.0 (n = 2), ExaVir Load v3 (n = 2), and NucliSens EasyQ v2.0 (n = 1). All currently available HIV VL assays are of sufficient sensitivity to detect plasma virus levels at a lower detection limit of 1,000 copies/mL. Bias data comparing the Abbott RealTime HIV-1, TaqMan v2.0 to the Amplicor Monitor v1.5 showed a tendency of the Abbott RealTime HIV-1 to under-estimate results while the TaqMan v2.0 overestimated VL counts. Compared to the Amplicor Monitor v1.5, 2-26% and 9-70% of results from the Versant bDNA 3.0 and Abbott RealTime HIV-1 differed by greater than 0.5log10. The average intra and inter-assay variation of the Abbott RealTime HIV-1 were 2.95% (range 2.0-5.1%) and 5.44% (range 1.17-30.00%) across the range of VL counts (2log10-7log10). Conclusions This review found that all currently available HIV VL assays are of sufficient sensitivity to detect plasma VL of 1,000 copies/mL as a threshold to initiate investigations of treatment adherence or possible treatment failure. Sources of variability between VL assays include differences in technology platform, plasma input volume, and ability to detect HIV-1 subtypes. Monitoring of individual patients should be performed on the same technology platform to ensure appropriate interpretation of changes in VL. Prospero registration # CD42013003603.